Flow chemistry. - Darvas, F.; Dormán, G. (György); Hessel, Volker (Walter de Gruyter GmbH, 2014)
This book fills the gap in graduate education by covering chemistry and reaction principles along with current practice, including examples of relevant commercial reaction, separation, automation, and analytical equipment. The Editors of Flow Chemistry are commended for having taken the initiative to bring together experts from the field to provide a comprehensive treatment of fundamental and practical considerations underlying flow chemistry. It promises to become a useful study text and as well as reference for the graduate students and practitioners of flow chemistry. Broader theoretical insight in driving a chemical reaction automatically opens the window towards new technologies particularly to flow chemistry. This emerging concept promotes the transformation of present day's organic processes into a more rapid continuous set of synthesis operations, more compatible with the envisioned sustainable world. These two volumes Fundamentals and Applications provide both the theoretical foundation as well as the practical aspects. --